2022
DOI: 10.1080/22221751.2022.2076616
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of rapid antigen tests on SARS-CoV-2 transmission in the fifth wave of COVID-19 in Hong Kong in early 2022

Abstract: The fast-spreading Omicron variant of SARS-CoV-2 overwhelmed Hong Kong, causing the fifth wave of COVID-19. It remains to be determined what mitigation measures might have played a role in reversing the rising trend of confirmed cases in this major outbreak. The government of Hong Kong has launched the mass rapid antigen tests (RAT) in the population and the StayHomeSafe scheme since February 2022. In this study, we examined the impact of the mass RAT on disease transmission and the case fatality ratio. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…But epidemiological population‐level measures (e.g. the basic reproduction number) usually hide immense variation at the individual level (Du, Hong et al., 2022 ; Du, Javan et al., 2020 ; Du, Liu et al., 2022 ; Du, Tian et al., 2022 ; Du, Xu et al., 2020 ). We thus carried out a systematic review and meta‐analysis of 17 studies on the dispersion parameter to characterize COVID‐19 superspreading.…”
Section: Discussionmentioning
confidence: 99%
“…But epidemiological population‐level measures (e.g. the basic reproduction number) usually hide immense variation at the individual level (Du, Hong et al., 2022 ; Du, Javan et al., 2020 ; Du, Liu et al., 2022 ; Du, Tian et al., 2022 ; Du, Xu et al., 2020 ). We thus carried out a systematic review and meta‐analysis of 17 studies on the dispersion parameter to characterize COVID‐19 superspreading.…”
Section: Discussionmentioning
confidence: 99%
“…This situation indicated a higher possibility of Omicron variant breakthrough infection after inactivated vaccine vaccination with more severe and fatal cases. Surprisingly, recent studies have shown that three-dose inactivated vaccine could provide protection efficacy of 98.1% against Omicron-induced severe symptoms and death, similar to the 98.3% efficacy of the mRNA vaccine, in elderly people (> 60 years old) [23][24][25] . The inactivated vaccine was also found to have better protective efficacy in the real world than expected based on an immunogenicity study.…”
Section: Introductionmentioning
confidence: 99%
“…Test strategies based on the detection of either viral nucleic acids, primarily by quantitative reverse transcription polymerase chain reaction (qRT-PCR), or of the viral nucleocapsid protein by rapid antigen tests (RATs) contribute to COVID-19 diagnosis and the control of SARS-CoV-2 transmission. This is exemplified by the recent management of the 5th pandemic wave caused by Omicron-BA.1 in Hong Kong [1]. A prerequisite for effective health care interventions is a good sensitivity (> 80%) and high specificity (> 97%) of such RATs fulfilling the minimal criteria set by the Word Health Organization (WHO), especially for RATs recommended for layman's use [2].…”
Section: Introductionmentioning
confidence: 99%